Local area networks : - Goldman, James E. (John Wiley & Sons, Inc., 2000)
Learn how to install, manage, and maximize business LANs! Fully updated to reflect the latest developments in the field, this comprehensive, business-oriented guide presents all the information you need to successfully implement and trouble-shoot LAN-based client/server information systems. Inside, you'll find in-depth, up-to-the-minute coverage of the theory, concepts, technology, installation, and management of business LANs. Most importantly, this new Second Edition underscores solutions to LAN challenges faced in today's business environments. Business cases in every chapter will help you develop effective analytical and design skills. Working models, such as the OSI Model, Top Down Model, and Client/Server Architecture Model, provide you with an effective framework for approaching problems and finding solutions. And an accompanying CD-ROM includes a wealth of background material on client/server information systems.